Numerical Study on the Effect of Mean Pressure and Loop's Radius to the Onset Temperature and Efficiency of Traveling Wave Termoacustic Engine - Endang Dian Rokhmawati; Irna Farikhah; Ummi Kaltsum; Harto Nuroso; Aan Burhanudin; Yuris Setyoadi; Muhammad Amiruddin; Irfan Abd Rahim (Universitas Muhammadiyah Magelang, 2020)
The thermoacoustic engine can be a device to convert waste heat energy in the engine car become useful energy such as for charging battery in car or Air conditioner of the car. This work can be done by experimentally and numerically. There are some parameters that have an impact on the performance of the engine. They are geometry of the engines, working fluid, and mean pressure. The performance of the engine depends on the efficiency and the heating temperature. In the car, waste heat energy is not high enough. Therefore, we need to utilize the low heating temperature to be converted into useful energy. This study contributes to numerically the effect of mean pressure and loop’s radius of the regenerator on the onset temperature and the efficiency of traveling wave thermoacoustic engines. The application that is used to solve numerical problems is fortran95. There are two codings that are used in fortran95. They are stability limits and efficiency codes. The lowest onset temperature that achieved is 153ËšC with efficiency up to 38.1% that can be reached when the mean pressure is 4.0 MPa and the loop's radius is 5 cm. This result indicated that we can use low heating temperatures from waste heat of engine car to turn on electronics equipment inside the car.